A narrative review of the analysis of nanoparticulate systems in the formulation and efficacy of antitumor drugs (Research, Society and Development, 2024)
The treatment of cancer remains a significant challenge in the healthcare field due to the side effects of conventional treatments and the need for more effective therapies. Nanotechnology offers a promising approach to overcome these limitations, with the development of nanoparticles as carriers of antitumor drugs. This article comprehensively reviews the use of nanoparticles in cancer therapy, from the definition of nanotechnology to the potential toxicity of nanoparticles. We discuss the different types of nanoparticles used, such as polymer-based nanoparticles, lipid-based nanoparticles, nanoemulsions, and gold nanoparticles, highlighting their advantages and applications in the delivery of antitumor drugs. Additionally, we explore conventional cancer treatments, such as surgery, radiotherapy, and chemotherapy, comparing their efficacy and side effects with nanotechnology-based treatments. Finally, we discuss the efficacy of antitumor drugs of nanotechnological origin and the challenges related to the potential toxicity of nanoparticles. This review provides a comprehensive and updated overview of the role of nanoparticles in cancer therapy, highlighting their potential to improve clinical outcomes and patient quality of life. Thus, the objective of this article is to present a systematic review of the use of nanoparticulate systems as antitumor drugs.